The effect of saturated and unsaturated fatty acid composition in bio-based lubricant to the tribological performances using four-ball tribotester - Zulhanafi P. (2024)
The performances of bio-based lubricants were influenced by the strength of its molecular interaction between the fatty acid chain and iron molecules on metal surfaces. In this study, the fatty acid compositions of refined, bleached and deodourised palm oil (RBDPO), double fractionated palm olein (SPL) and palm mid olein (PMO) were determined by using gas-liquid chromatography (GLC). Four-ball tribotester was used to evaluate the performance of the lubricants in terms of friction coefficient, wear scar diameter (WSD) and surface roughness (Ra). It was found that PMO with high saturated fatty acid content exhibited excellent tribological characteristics subjected to various temperatures and rotational speeds. However, there was no significant impact observed at extreme pressure (EP) conditions. The physical wear condition was also discussed and analysed.